2010
DOI: 10.1182/blood-2009-09-244251
|View full text |Cite
|
Sign up to set email alerts
|

Many chronic lymphocytic leukemia antibodies recognize apoptotic cells with exposed nonmuscle myosin heavy chain IIA: implications for patient outcome and cell of origin

Abstract: Many B-cell chronic lymphocytic leukemia (CLL) monoclonal antibodies (mAbs) can be grouped into subsets based on nearly identical stereotyped sequences. Subset 6 CLL mAbs recognize nonmuscle myosin heavy chain IIA (MYHIIA). Herein, we report that during apoptosis, MYHIIA becomes exposed on the cell surface of a subgroup of apoptotic cells, allowing subset 6 CLL mAbs to bind with it. Because other non-subset 6 CLL mAbs interact with apoptotic cells, 26 CLL mAbs, including 24 not belonging to subset 6, were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
156
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 46 publications
(76 reference statements)
5
156
0
7
Order By: Relevance
“…Treatment of patients who relapse with leukemia, lymphoma, or multiple myeloma after allogeneic transplantation with donor T cells has illustrated that cellular immunotherapy can lead to complete eradication of cancer cells, resulting in cure of the disease. 1 In the nontransplantation situation, an immune response from donor T cells recognizing alloantigens on hematopoietic cells from the patient will lead to destruction of the patient's hematopoietic system. If the malignant counterpart of these cells also expresses these alloantigens on their cell membrane, this immune response will also eradicate hematopoietic cancer cells.…”
Section: J H Frederik Falkenburg Leiden University Medical Centermentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of patients who relapse with leukemia, lymphoma, or multiple myeloma after allogeneic transplantation with donor T cells has illustrated that cellular immunotherapy can lead to complete eradication of cancer cells, resulting in cure of the disease. 1 In the nontransplantation situation, an immune response from donor T cells recognizing alloantigens on hematopoietic cells from the patient will lead to destruction of the patient's hematopoietic system. If the malignant counterpart of these cells also expresses these alloantigens on their cell membrane, this immune response will also eradicate hematopoietic cancer cells.…”
Section: J H Frederik Falkenburg Leiden University Medical Centermentioning
confidence: 99%
“…1 First, MEAC binding inversely correlated with IGHV gene mutational status. Indeed, 15 of 16 MEAC-reactive CLL mAbs carried unmutated IGHV genes.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It is worthy of note that these structures may also share molecular identity with epitopes on infectious pathogens (molecular mimicry). 2,11,25 In mice and men, natural germ-line Abs bind to these oxidation-specific epitopes and IgM anti-oxLDL Abs are frequently found in the circulation of healthy persons. 1 For this reason, we have proposed that CLL cells may be derived from self-reactive natural Ab-producing B cells that are part of the innate first-line defence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by using recombinant DNA technologies, the role of antigenic reactivity and the impact of somatic hypermutation (SHM) on CLL mAb specificity have been investigated and revealed that CLL cells likely derive from B cells producing polyreactive, natural antibodies encoded by germline IG genes which either retain or lose polyreactivity due to SHM (26)(27)(28). Although the accumulated data on antigen reactivity does not provide the definitive agent driving CLL, they do provide a framework from which comparisons between other entities, most notably autoimmune diseases, can be drawn.…”
Section: Introductionmentioning
confidence: 99%